2018
DOI: 10.21149/9057
|View full text |Cite
|
Sign up to set email alerts
|

Diseño y validación de un score para detectar adultos con prediabetes y diabetes no diagnosticada

Abstract: Objetivo. Diseñar y validar un score de riesgo de fácil apli­cación para detectar prediabetes y diabetes no diagnosticada en población mexicana. Material y métodos. Empleando la información del estudio de cohorte de 10 234 adultos del Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán (INCMNSZ), se identificaron factores de riesgo incluidos en modelos de regresión logística múltiple estrati­ficados por sexo. Los coeficientes beta fueron multiplicados por 10 para obtener el peso de cada variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(43 reference statements)
0
1
1
1
Order By: Relevance
“…In this study, a 15% frequency of glucose intolerance (prediabetes) was observed, which is lower than that reported in other countries, including Mexico, where it varies from 19.9 to 43.2% ( 17 18 , 20 – 21 ) in similar samples and in the general population, but higher than the frequency of 6.7% found in Ecuador ( 22 ) . The frequency found in this study is higher than that reported in 2018, which mentions that about 7.5% of adults in Mexico have prediabetes ( 23 ) . Based on these findings, solutions could be sought to minimize the alterations observed in these health workers who are at great risk of developing diabetes in the next 10 years, in order to delay the progression of the disease and avoid cardiovascular complications ( 14 ) .…”
Section: Discussioncontrasting
confidence: 81%
“…In this study, a 15% frequency of glucose intolerance (prediabetes) was observed, which is lower than that reported in other countries, including Mexico, where it varies from 19.9 to 43.2% ( 17 18 , 20 – 21 ) in similar samples and in the general population, but higher than the frequency of 6.7% found in Ecuador ( 22 ) . The frequency found in this study is higher than that reported in 2018, which mentions that about 7.5% of adults in Mexico have prediabetes ( 23 ) . Based on these findings, solutions could be sought to minimize the alterations observed in these health workers who are at great risk of developing diabetes in the next 10 years, in order to delay the progression of the disease and avoid cardiovascular complications ( 14 ) .…”
Section: Discussioncontrasting
confidence: 81%
“…La prevalencia de descontrol de la diabetes fue estratificada por sexo y edad (<50 y >=50 años), para fines comparativos con otros estudios y considerando las limitaciones del tamaño de muestra (personas con diabetes diagnosticada, n=441). 19 Para estimar la asociación entre diabetes total y descontrol glucémico y los factores asociados, se calcularon razones de prevalencia usando modelos de regresión de Poisson. 20 El primer modelo incluyó variables socioeconómicas y salud pública de méxico / vol.…”
Section: Análisis De Datosunclassified
“…A more objective measure of competence in our program would be assessing changes in the degree to which trainees conducted implementation research from baseline to training completion. Although we only assessed this at training completion, results are encouraging: as of November 2018, 38 in-country projects were completed, 15 were ongoing, and 8 manuscripts and 1 book chapter were published (3442). These achievements are evidence of the program’s potential to energize trainees’ careers, contribute to their professional development, and nurture competence to address noncommunicable diseases.…”
Section: Implications For Public Healthmentioning
confidence: 99%